G16 The Paediatric Observation Priority Score (POPS): a more accurate predictor of admission risk from the Emergency Department than the Manchester Children's Early Warning System (ManChEWS). (7th April 2014) - Rowland, AG; Cotterill, S; Lees, H; Kelly, J
Abstract : Background: The Paediatric Observation Priority Score (POPS) is a specific Emergency Department (ED) physiological and observational aggregate scoring system, with scores of 0–18. A higher score indicates greater likelihood of admission. The Manchester Children's Early Warning System (ManChEWS) assesses six physiological observations to create a trigger score, classified as Green, Amber or Red. Methods: Prospectively collected data were used to calculate POPS and ManChEWS on 2068 patients aged under 16 (mean 5.6 years, SD 4.6) presenting over one month to a UK District General Hospital Paediatric ED. Logistic regression and ROC comparison, using STATA 11, were used to investigate the ability of ManChEWS and POPS to predict admission to hospital within 72 h of presentation to the ED. Results: Comparison of the area under the Receiver Operating Characteristics (ROC) curve indicates that the ManChEWS ROC is 0.67 (95% CI 0.65 to 0.70), SE 0.02, and the POPS ROC is 0.72 (95% CI 0.69 to 0.75), SE 0.02. The difference is statistically significant (p < 0.01). At a POPS cut-off of ≥2, 80% of patients had their admission risk correctly classified (Positive Predictive Value (PPV) of POPS 2, 38.94%) whereas for ManChEWS with a cut off of ≥Amber only 71% of patients were correctly classified (PPV of ManChEWS Amber, 29.06%). Conclusions: POPS is a more accurate predictor of admission risk from the ED than ManChEWS and is more suitable to use in an ED setting. Replacing ManChEWS with POPS would appear to be clinically appropriate in a Paediatric ED and multi-centre validation of this proposal would be helpful.